UI Greenmetric Data Review: A workshop on ranking improvement - Norhidayah, Mohamad (2017)
18 September, A workshop and data reviewing session for UI Greenmetric Ranking was held at Banquet Hall, Tun Abdul Razak Chancellory on 18 September 2017. Main objective for this workshop is to give exposure to all the head of departments involved on the roles and responsibility that they have to play for the betterment of UMP ranking in UI Greenmetric.